An Efficient, Green, and Solvent‐free Multi‐component Synthesis of Benzimidazolo/Benzothiazolo Quinazolinone Derivatives Using Sc (OTf)3 Catalyst Under Controlled Microwave Irradiation. (11th September 2018) - Gajaganti, Somaiah; Kumari, Savita; Kumar, Dhirendra; Allam, Bharat Kumar; Srivastava, Vandana; Singh, Sundaram
Abstract : An efficient, fast, and green synthesis of benzimidazolo/benzothiazolo quinazolinone derivatives has been developed under solvent‐free conditions by the reaction of 2‐aminobenzimidazole/2‐aminobenzothiazole, aromatic aldehydes, and 1, 3‐diketones. This method extended the application of microwave irradiation and scandium triflate combination and also tenders a lot of benefits such as excellent product yields, shorter reaction time, easy isolation of products, and environmentally benign reaction conditions. Abstract :